(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
Inclusive education is a process that integrates students with special needs in mainstream schools, providing them with appropriate support and adaptations. This paper discusses the differences between mainstream and special education, focusing on the right to education, aims and approaches, responsibilities and competences, curricula, focus of education, teacher preparation, learning conditions, teaching methods, learning standards, assessment and evaluations, teacher competencies, educational research and legislation. In Macedonia, inclusive education started in 1998 and is still in the process of development, aimed at the full inclusion of students with disabilities, which is stipulated in the Law on Basic Education passed in 2019. The methodology includes an analysis of existing research and laws, as well as a comparative study of regular and special education. Data from relevant sources such as European and national education agencies, UNICEF reports and laws on special education were used. This methodology enables a detailed overview of the current situation and challenges in inclusive education. The conclusion is that although significant efforts have been made for the integration of students with special needs in mainstream schools, there are many challenges that need to be overcome. Better support for teachers, more resources and funding, and a change in attitudes of the society are needed. With appropriate measures and policies, real inclusion and quality education for all students can be achieved.